(untitled) (Malay Literature, 2016)
This paper attempts to provide an alternative perspective of Abdullah Hussain’s Interlok (2010) by examining the original version of the novel published in 1971. Exploring the controversy through claims made by the general public, academics and experts through the Internet, we argue that those who found the novel racist in essence are themselves guilty of racism. The paper will further suggest that Abdullah Hussain is a fierce nation builder who attempts to redefine the nation’s idea of citizenship and nationhood that can be explained by using the Race Relations Cycle theory. Most importantly, the article demonstrates the writer’s desire to try and redefine citizenship among the Malaysian people by deconstructing well-perceived stereotypical race constructions and promoting unity in a new nation. Keywords: Interlok, racism, nationalism, Abdullah Hussain